Environmental-friendly underwater acoustic communication and networks - Jesus, S. M. (2014)
Intense harvesting of ocean resources extended exploitation activities to previously unexplored open ocean areas, to greater ocean depths and to remote polar regions. Such activities include, but are not limited to, energy, geology and fisheries. In practice, not only the number of working platforms at sea has increased dramatically, but their structure is more complex with multi sites, interconnecting pipes, cables, remote sensors and mobile platforms. In many cases, each exploitation site represents a complex submerged infrastructure requiring timely maintenance, protection and monitoring. An underlying requirement for efficient protection and monitoring of such infrastructures is the existence of reliable communications which, for submerged and untethered platforms, can only be done acoustically. So, underwater acoustic communications became an enabler for many ocean activities. More, with the multiplication of agents in geographically limited areas point-to-point communications quickly evolved to the necessity of communication networks. The European Union has recently published a marine strategy directive aiming at defining the concept of "good environmental status". Among others, one of the descriptors directly addresses the amount of acoustic energy in the ocean. Acoustic energy sources combine along time and range to form what is normally termed as ocean soundscape (or ambient noise). As we know, measurement and/or monitoring of ocean noise is a complex task since there are a large number of indicators to be taken into account to characterize the wide variety of noise types according to their origin, duration, intensity, frequency, directional properties, etc. It is undeniable that anthropogenic noise has increased steadily in the last decades as a result of the increase of 1) the ship traffic (in number of ships, size and speed) and 2) the number of work platforms at sea, most of which for fossil and/or renewable energy generation. The impact of this underwater sound pressure increase on marine life and biodiversity is still under assessment. Estimating the "good environmental status" in offshore activities requires a complete Environmental Impact Assessment (EIA) structure with complex surveillance routines, multi parameter data recording and multi site sensing. EIA aims at monitoring the emission of pollutants, contaminants, preserving marine life and preventing environmental disasters either man made or due to natural conditions. Efficient EIA employs underwater acoustics as a means for communicating to remote nodes and to underwater mobile platforms. Whether underwater acoustic communications usage under EIA is harmful for marine life thus contributing to the deterioration of the "good environmental status" is an open question. This talk reports the underwater acoustic communications work carried out at Larsys, in collaboration with Underwater Acoustic Network (UAN) project partners in the last few years. This includes the ongoing combat to Intersymbol Interference (ISI) and signal loss by signal coherent recombination in time, frequency and, recently, in angle. The basic tool is the usage of the passive time-reversal concept. The usage of ISI-reduction techniques for mobile node communications in underwater networks was tested in a open sea full size deployment as part of the UAN project, during a sea trial that took place in the Strindfjord, Trondheim (Norway), at the end of May of 2011. Future work intends to address two topics: one is the reduction of the dependence of a vertical hydrophone array for passive time reversal processing, by exploring "compact" vector sensor arrays and the other is to investigate biological acoustic noise as a potential signal interference source for underwater acoustic communication signals and networks.